SOCIO-ECONOMIC PROFILE OF THE CHAR AREAS IN KAMRUP DISTRICT, ASSAM - Alom, Md Shamsul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The char areas of Assam, formed by the river Brahmaputra, are among the most backward regions of the state. This study examines the socio-economic profile of char dwellers in Kamrup district, focusing on their demographic features, education, livelihood, health and housing and development challenges. The findings show that char households are large and face frequent displacement due to floods and erosion. Literacy is much lower than the state average, especially among girls. Agriculture is the main occupation but remains insecure, forcing many people to migrate seasonally for work. Health services are inadequate, sanitation is poor and housing is fragile. Women suffer from early marriage, poor healthcare and lack of property rights. Government schemes exist but their implementation is weak. NGOs provide limited support through boat schools and mobile health units. Overall, char dwellers remain marginalized, and inclusive development policies are urgently required.